The Influence of the Work Environment, Motivation and Leadership on the Performance of Millenial Academic Employees During Pandemic Covid-19 - Yohana F. Cahya Palupi Meilani (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
This study aims to determine the effect of work environment and leadership on employee performance, work environment and leadership on employee motivation, motivation on millennial generation performance at XYZ Private College. The phenomenon of an increase in permanent academic employees (lecturers and academic staffs) at the age of the millennial generation at PTS XYZ. Then there are efforts to improve towards superior accreditation from B accreditation as a form of performance for millennial lecturers and staffs at PTS XYZ during the Covid-19 pandemic. The research conducted is a quantitative study with the respondents being permanent employees of the millennial generation (lecturers and academic staffs) who have worked for at least 2 years. Collecting data using a questionnaire measuring instrument using a Likert scale of 1 – 5. The data analysis method used the Structural Equation Model (SEM) with Smart-PLS software in processing the data for 150 respondent. The results showed that the work environment and leadership had a positive influence on employee motivation. Work environment, leadership and motivation of employees have a positive influence on employee performance. This research is related to employee performance so that it can be used as consideration for similar private universities in an effort to improve the performance of millennial generation employees and become a reference for further research.